The Role of Long Non-Coding RNAs in Epithelial-Mesenchymal Transition-Related Signaling Pathways in Prostate Cancer - Shen, Dexin; Peng, Hongwei; Xia, Caixia; Deng, Zhao; Tong, Xi; Wang, Gang; Qian, Kaiyu (Frontiers in Molecular Biosciences, 2022)
Prostate cancer (PCa) is one of the most common male malignancies with frequent remote invasion and metastasis, leading to high mortality. Epithelial-mesenchymal transition (EMT) is a fundamental process in embryonic development and plays a key role in tumor proliferation, invasion and metastasis. Numerous long non-coding RNAs (lncRNAs) could regulate the occurrence and development of EMT through various complex molecular mechanisms involving multiple signaling pathways in PCa. Given the importance of EMT and lncRNAs in the progression of tumor metastasis, we recapitulate the research progress of EMT-related signaling pathways regulated by lncRNAs in PCa, including AR signaling, STAT3 signaling, Wnt/β-catenin signaling, PTEN/PI3K/AKT signaling, TGF-β/Smad and NF-κB signaling pathways. Furthermore, we summarize four modes of how lncRNAs participate in the EMT process of PCa via regulating relevant signaling pathways.